Tom Clancy weapons grade - Bentley, Don; Clancy, Tom, 1947-2013 (New York : Berkley, 2024)
The quiet of a Texas night is shattered by the sounds of screeching brakes, crumpling metal and...automatic-weapons fire? When Jack Ryan Jr. stumbles across what first appears to be a simple car accident, he never imagines that he will quickly be entangled in an international conspiracy that threatens his very life.
Keywords: Ryan, Jack, -- Jr. (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Conspiracies -- Fiction; Cold cases (Criminal investigation) -- Fiction; Assassins -- Fiction; Texas -- Fiction; Thrillers (Fiction); Spy fiction; Action and adventure fiction